Endoplasmic Reticulum Stress in Endometrial Cancer - Ulianich, Luca; Insabato, Luigi (Frontiers in Medicine, 2014)
Endometrial cancer is a common gynecologic malignancy often diagnosed at early stage. In spite of a huge advance in our understanding of endometrial cancer biology, therapeutic modalities do not have significantly changed over the past 40 years. A restricted number of genes has been reported to be mutated in endometrial cancer, mediating cell proliferation and invasiveness. However, besides these alterations, few other groups and ourselves recently identified the activation of the Unfolded Protein Response (UPR) and GRP78 increase following Endoplasmic Reticulum (ER) stress as mechanisms favoring growth and invasion of endometrial cancer cells. Here a concise update on currently available data in the field is presented, analyzing the crosstalk between the UPR and the main signaling pathways regulating endometrial cancer cell proliferation and survival. It is evident that this is a rapidly expanding and promising issue. However, more data are very likely to yield a better understanding on the mechanisms through which endometrial cancer cells can survive the low oxygen and glucose tumor microenvironment. In this perspective, the UPR and, particularly, GRP78 might constitute a novel target for the treatment of endometrial cancer in combination with traditional adjuvant therapy.